Analysis of the Influence of the UP3AI Program on the Ability to Read the Qur'an and the Formation of USK Students' Morals - Muchlinarwati, Muchlinarwati; Zilkifli, Muhammad Yusuf; Muttaqin, Reza; NK, Mahdi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study was conducted based on the fact that several USK students still cannot read the Quran and do not understand the correct Makhraj of letters and the laws of tajwid. Therefore. USK has a UP3AI (Islamic Religion Course Development Unit) program, a companion program development unit for Islamic religious courses aimed at forming a Quranic generation with noble character. This study aims to analyze the effectiveness of the UP3AI program in improving USK students' ability to read the Quran and its impact on moral formation. The research method uses a mixed approach (quantitative and qualitative). The results show that the program's effectiveness is not optimal due to constraints on time discipline, communication, and mentor abilities, and it is said to be effective if the learning process between mentors and students has gone well. Then there is the quality of teaching the Quran, both in the mosque and the Musalla; there is no stable teaching method, limited hours of teaching the Quran, the elimination of the teaching curriculum, the influence of television shows, and others that cause the success of this program not to be achieved. In addition, the impact on student morals is not significant.